Changes In Pm2.5 Levels After Covid-19 Outbreak In Malaysia - Razali, Wan Ahmad Asyraf Wan Mohd (Universiti Sains Malaysia, 2021)
The COVID-19 pandemic was caused by a highly infectious coronavirus, which prompted global control measures such as social isolation and lockdowns. By reducing human activity, COVID-19 management efforts have led in enhanced air quality locally and globally in the near term. We investigated the impact of Movement Control Order (MCO) towards the air quality in 10 stations, which is Alor Setar, Seberang Perai, Cheras, Petaling Jaya, Bandaraya Melaka, Pasir Gudang, Kuala Terengganu, Tanah Merah, Kota Kinabalu, and Kuching. The areas chosen are the urban and industrial zones in Malaysia. The aim of the study is to compare level of PM2.5 concentrations at urban and industrial areas before and during Movement Control Order (MCO) and to identify changes of PM2.5 daily trend based on different MCO phase. Additionally , it is also to investigate the relationship of PM2.5 concentration level before MCO and during MCO with different restriction phase. The data is collected from the Department of Environment (DOE). From the research, it is found that most of the stations experienced reduction in PM2.5 levels. For North Region, the highest PM2.5 level is during MCO at 164.642 μg/m3. For East and West Coast regions, the highest concentration of PM2.5 are during the PRE MCO phase which recorded at 107.307 μg/m3 and 113.108 μg/m3 respectively. Meanwhile for South and East Malaysia Region, the highest concentration are during CMCO at 121.986 μg/m3 and 155.132 μg/m3 respectively. The discrepancy in PM2.5 level trends between each regions may be caused by the existence of numerous industries near the stations' locations. Certain industries may be closed due to government regulations, while others may remain open due to recognized as essential services.